Across the Board: Federico Bella on Electrochemical Nitrogen Reduction. Issue 11 (4th May 2020) - Bella, Federico
Abstract: In this series of articles, the board members of ChemSusChem discuss recent research articles that they consider of exceptional quality and importance for sustainability. This entry features Prof. F. Bella, who discusses the electrochemical reduction of nitrogen to produce ammonia through the addition of protons and electrons under mild conditions (25 °C, 1 atm). This reaction has the potential to replace the energy‐intensive traditional Haber–Bosch process but faces several challenges and pitfalls. Abstract : Chasing the dream : Our board member Prof. Federico Bella discusses electrochemical reduction of nitrogen (E‐NRR) as an alternative to the Haber–Bosch process to produce ammonia. Despite some remaining challenges, E‐NRR might allow the production of ammonia under mild conditions (25 °C, 1 atm) through the addition of protons and electrons.